Experimental investigation on surface tension of metal oxide-water nanofluids - Bhuiyan, M.H.U.; Saidur, R.; Mostafizur, R.M.; Mahbubul, I.M.; Amalina, M.A. (Elsevier, 2015)
"Nanofluids", smart fluids with advanced thermal properties, have proved their promising potential in enhancing the heat transfer performance of a thermal system as well as mitigating the energy crisis of the universe. Besides all other's thermo-physical properties, surface tension governs the transport of the liquid and plays a crucial role in the heat transfer. However, the studies on the effect of surface tension on the performance of nanofluids are quite a few and demonstrated debatable results. Therefore, the present experimental study attempts to determine the surface tension of the nanofluids by dispersing Al2O3, TiO2, and SiO2 nanoparticles in Distilled Water (DW). The experiment was conducted by using the most common Du-Hotly ring method in DCAT11EC automatic surface tensiometer. In this study, the authors analyzed all the possible effects on surface tension of nanofluids with the change in concentrations (from 0.05 to 025 vol.) and temperatures (from 30 degrees C to 50 degrees C), as well as the impact of various nanoparticles along with their sizes. The results indicate that the surface tension of the nanofluids increases with concentration, whereas decreases with the increase in temperature. Besides, the smaller nanoparticles exhibit lower surface tension than the larger ones. All in all, the surface tension of the nanofluids augments from 3.1 to 7.8 in compared with the base fluid for concentrations of 0.05 vol. to 0.25 vol. and temperatures of 30 degrees C to 50 degrees C, in all cases. (C) 2015 Elsevier Ltd. All rights reserved.